Questions réponses pour les révisions ...

Question d'Eva :
Calculer la dérivée de \(f: x\mapsto \ln (x)-3\left(\ln x \right)^2\)

\(f= u+v\) où \(v(x) = ln(x)\) et \(v(x) = -3\left(\ln x \right)^2\)
on a  alors \(u'(x) =\dfrac{1}{x}\) et \(v'(x)= -3 \times 2\ln x \times \dfrac{1}{x}\)
En effet \(v=-3a^2\), donc \(v'=-3\times 2 aa'=-6aa'\)
On a alors \(f'(x)= \dfrac{1}{x}-6\dfrac{\ln x}{x}\)

\[ f'(x)=\dfrac{1-6\ln x}{x}\]

ImprimerE-mail

Statistiques

Visiteurs
154
Articles
1395
Compteur d'affichages des articles
6664505